EFFECTS OF GRADED DILUTED DOSES OF GRAMOXONE HERBICIDE ON PROGESTERONE, TESTOSTERONE, ALBUMIN AND TOTAL PROTEIN OF MALE AND FEMALE ALBINO RATS (Rattus norvegicus) - Agbeyi, Erhomarhua Victor; Oghenerhoro, Patrick Suit (FUDMA JOURNAL OF SCIENCES, 2025)
The use of herbicides no matter how diluted it maybe, may have physiological effects on mammals. This work tends to examine the effects dilution factor of 104 of a 10-fold serial dilution of gramoxon herbicide graded into 0.25, 0.5 and 0.75 mg/kg body weight, orally administered to twenty male and twenty female rats has on progesterone, testosterone, albumin and total protein of the rats. The weights of the rats ranges between 79 -119g and were divided randomly into group A, B, C and D. Each group has 10 animals, 5 male and 5 female. Group A is the control. Group A, B.C and D were fed with feed and water ad libitum. Group B, C and D were administered 0.25, 0.5 and 0.75mg/kg bw dose respectively. After 28 days the rats were sacrificed and blood collected into EDTA bottles for laboratory assessment. Computer based ANOVA excel showed that albumin and total protein revealed a significant difference (p<0.05) in group B (0.25mg/kg bw), C (0.5mg/kg bw) and D (0.75mg/kg bw) in both sex compared with control. Testosterone and progesterone level showed a significant decrease (p<0.05) compared with control in group B, C and D. The results clearly indicated that gramoxon herbicide has biochemical and reproductive effects on albino rats even at 10-fold dilution.